Interview with Franci Duran about her Video Art Installation 8401 - Duran, Franci; Schniedermann, Wibke; Justus Liebig University Giessen (My University, 2018)
8401 is a video installation that includes a video loop showing images of a building and the streets in front. Depending on the room in which the installation is being shown, there are one or more devices playing sound files. The image or images of the video shift slowly but constantly, and they look a bit like a collage made from the snippets of different pictures. You can watch part of the video used for the installation on the website of On_Culture (https://www.on-culture.org/journal/perspectives/duran-schniedermann-8401/) by entering the password watch8401. Make sure you have speakers or headphones to hear the audio track, which is an integral part of the experience.
Keywords: Chile; Google; human rights; media art installation; memory; ddc:300